Effect of Brace Design on Patients with ACL-Ruptures - Strutzenberger, G.; Braig, M.; Sell, S.; Boes, K.; Schwameder, H. (International Journal of Sports Medicine, 2012)
Different designs of functional knee braces for ACL-injury rehabilitation exist. In addition to the mechanical stabilization provided by rigid shell braces, sleeve braces also address proprioceptive mechanisms, but little is known if this leads to benefits for ACL-deficient subjects. Therefore the aim of this study was to investigate the effect of 2 different functional brace designs (shell and sleeve brace) on functional achievements in ACL-deficient patients. 28 subjects with ACL-ruptured knees performed tests for knee joint laxity, joint position sense, static and dynamic balance and isometric and dynamic lower limb extension strength in non-braced, sleeve braced and shell braced condition. The results showed a significant decrease in knee joint laxity for sleeve (33%; p<0.001) and rigid shell bracing (14%, p=0.039). The sleeve brace revealed a significant increase in dynamic balance after perturbation (20%; p=0.024) and a significant increase in dynamic lower limb peak rate of force development (17%; p=0.015) compared to the non-braced condition. The effects might be caused by the flexible area of support and the incorporated mechanisms to address proprioceptive aspects. Braces might not be needed in simple daily life tasks, but could provide beneficial support in more dynamic settings when patients return to sporting activities after an ACL-injury.
Keywords: ACL-deficiency; functional bracing; proprioception; rehabilitation